The Problems of PAI Learning in the Era of Society 5.0 in Shaping Student Morality in Indonesia - Donna Fadhilah; Elan Sumarna; Mohammad Rindu Fajar Islamy (Bulletin of Science Education, 2024)
The very rapid development of digital technology in the last few decades has ushered students into the era of Society 5.0, namely an intelligent learning design in carrying out daily activities to improve learning with the help of technology. Problems that arise include the integration of religious values in a digital context, the decline in morality due to the influence of global culture, and difficulties in adapting the PAI curriculum to make it relevant to current developments. This research aims to analyze the impact of the Society 5.0 era on PAI learning and its implications for the formation of student morality. This research uses a qualitative approach with a literature study method. The findings from this research are that learning has a vital function in improving the performance of students' innovative thinking and strengthening interactions between teachers and students. Through this approach, character education in the era of society 5.0 can be realized efficiently. The conclusions of this research support students in understanding the essential character values in their digital life, including digital ethics, responsibility in cyberspace, collaboration, and critical performance in filtering the information received.